Theorizing rituals - Kreinath, Jens, 1967-; Snoek, Joannes Augustinus Maria, 1946-; Stausberg, Michael. (Numen Book Series, 2006)
Volume two of Theorizing Rituals mainly consists of an annotated bibliography of more than 400 items covering those books, edited volumes and essays that are considered most relevant for the field of ritual theory. Instead of proposing yet another theory of ritual, the bibliography is a comprehensive monument documenting four decades of theorizing rituals.